2006
DOI: 10.1590/s0004-27302006000300006
|View full text |Cite
|
Sign up to set email alerts
|

Valores inesperadamente elevados de TSH: a presença de formas de alto peso molecular ("macro TSH") deve ser investigada

Abstract: The laboratory methods usually employed for the measurement of serum TSH present sensitivity and specificity levels, both analytical and clinical, are highly satisfactory. Additionally, the methodologies are quite robust, so that false-positive and false-negative results are rare and unexpected. In this paper we describe two individuals quoted as euthyroid clinically, with no reference to autoimmune diseases, and no reference to the use of exogenous TSH, that presented with normal to extremely high serum TSH l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
0
2
0
2
Order By: Relevance
“…Although the immunoreactive band of IgG-TSH was shifted by the DTT treatment, detection of IgG2b at same molecular weight confirmed the existence of IgG-TSH complex even after DTT treatment (Figure 3J). In contrast to aforementioned treatments, only acidification below pH 3 has been reported to dissociate the macro-TSH complex in humans (Sakai et al, 2009; Vieira et al, 2006). Therefore, we also examined the effect of acidification on the stability of the mouse IgG-TSH complex.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the immunoreactive band of IgG-TSH was shifted by the DTT treatment, detection of IgG2b at same molecular weight confirmed the existence of IgG-TSH complex even after DTT treatment (Figure 3J). In contrast to aforementioned treatments, only acidification below pH 3 has been reported to dissociate the macro-TSH complex in humans (Sakai et al, 2009; Vieira et al, 2006). Therefore, we also examined the effect of acidification on the stability of the mouse IgG-TSH complex.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that PT-TSH forms macro-TSH with IgG or albumin. It is suggested that the binding of TSH to IgG is extremely high in humans and rats (Erhardt and Scriba, 1977; Kourides et al, 1978; Mori et al, 1984; Sakai et al, 2009; Vieira et al, 2006). For example, incubations with the surfactant Triton-X, the strong denaturants; mercaptoethanol and quinidine hydrochloride, or the enzyme trypsin do not dissociate the IgG-TSH complex.…”
Section: Resultsmentioning
confidence: 99%
“…Entretanto, ao solicitarmos um exame complementar jamais devemos esquecer a correlação clínico-laboratorial tão bem discutida no estudo de Vieira e cols. (6).…”
Section: P Carvalhounclassified
“…Há dados sugerindo que o TSH ligado a anticorpos também seja incapaz de se ligar às células tireóideas, o que corrobora os achados clínicos de Vieira e cols. (6), pois os pacientes não têm sinais e sintomas de hipertireoidismo ou bócio, apesar de apresentarem TSH elevado. Por outro lado, também não há características clínicas de hipotireoidismo, ou seja, uma fração do TSH sérico deve ser biologicamente ativa o que é fundamental para manter a função tireóidea normal.…”
Section: P Carvalhounclassified
“…The TSH did not recover more than 20% when subjected to polyethylene glycol precipitation (14). The Roche and Perkin-Elmer DELFIA assays are more susceptible to macro-TSH interference, whereas the ADVIA Centaur assay is less sensitive to such interference (16,17) Macro-TSH is diagnosed when a macro-TSH/ hypothyroid mixture gives lower TSH values after the incubation in assays known to be adequately sensitive to macro-TSH. The gold standard test for the isolation of macro-TSH is gel filtration chromatography which is costly and not readily available (18).…”
mentioning
confidence: 99%